Bias of maximum-likelihood estimates in logistic and Cox regression models: a comparative simulation study - Ingo Langner; Ralf Bender; Rebecca Lenz-Tönjes; Helmut Küchenhoff; Maria Blettner (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
Parameter estimates of logistic and Cox regression models are biased for finite samples. In a simulation study we investigated for both models the behaviour of the bias in relation to sample size and further parameters. In the case of a dichotomous explanatory variable x the magnitude of the bias is strongly influenced by the baseline risk defined by the constants of the models and the risk resulting for the high risk group. To conduct a direct comparison of the bias of the two models analyses were based on the same simulated data. Overall, the bias of the two models appear to be similar, however, the Cox model has less bias in situations where the baseline risk is high.
urn:nbn:de:bvb:19-epub-1737-8
Keywords: 519